2015
DOI: 10.1063/1.4908031
|View full text |Cite
|
Sign up to set email alerts
|

Lattice relaxation studies in strained epitaxial Fe-Co-C films

Abstract: Extraordinarily large perpendicular magnetic anisotropy in epitaxially strained cobalt-ferrite CoxFe3−xO4(001) (x = 0.75, 1.0) thin films Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…In order to stabilize bct structure above the thickness limit of method A ( t > 5 nm), our research group examined effects of adding various third elements as method B 24 . Other researchers also reported on results of third element addition including C, 19 B, 20 Ti, 21 and Mo 32 . Here we explain about effects of V and N addition as previously reported by our group in a patent application dated 2017 25 and a paper dated 2019 23 .…”
Section: Attempt At Fabrication Of Thicker Feco Films Using Methods Bsupporting
confidence: 79%
See 2 more Smart Citations
“…In order to stabilize bct structure above the thickness limit of method A ( t > 5 nm), our research group examined effects of adding various third elements as method B 24 . Other researchers also reported on results of third element addition including C, 19 B, 20 Ti, 21 and Mo 32 . Here we explain about effects of V and N addition as previously reported by our group in a patent application dated 2017 25 and a paper dated 2019 23 .…”
Section: Attempt At Fabrication Of Thicker Feco Films Using Methods Bsupporting
confidence: 79%
“…Giant magnetic anisotropy of FeCo compounds was theoretically predicted in 2004; 4 after that, the prediction was proven via a number of experiments with thin films 11–25 . This giant magnetic anisotropy can be explained by tetragonalization of the crystal structure and modification of the band structure 4 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is expected that films with lower thickness can exhibit slightly higher strain. In a recent publication byReichel et al [7,19], observed c/a ratios of up to. 1.05 in Fe-Co-C films with 2 at% C with 5 nm thickness.…”
Section: Resultsmentioning
confidence: 91%
“…Nevertheless, due to the strong tendency for the FeCo alloys to relax, it is difficult to maintain the tetragonal distortion induced by the underlying substrates for thin films thicker than 2 nm [6,7,8]. Recently, following the prediction based on DFT calculations [9,10], systematic studies have been performed on FeCo+X (X= C and B), where spontaneous tetragonal distortions with c/a=1.04 can be induced by a few atomic percent interstitial doping of C or B atoms occupying the octahedral interstitial sites. The resulting MAE can be as large as 0.5 MJ/m 3 with B concentration up to 4 at%, where the tetragonal strain reaches 5%.…”
Section: Introductionmentioning
confidence: 99%